Land After Luxury - Andrew Magnus (ARQ, 2022)
Land After Luxury’s speculative project explores questions of restitution and agroeconomic growth in the context of (post)colonial Puerto Rico. An apparent sovereign territory, the Caribbean island continues to be subjected to forced degrowth, austerity measures, and legacies of extraction, including leisure spaces. Inherited from the plantation and agricultural appropriation logic after the U.S. invasion in 1898, the project considers the current golf course landscapes as symbolic places of colonial representation and offers agroecological and architectural interventions to support a sovereign form of localized growth.